A political memoir of the Anglo-French condominium of the New Hebrides - Woodward, Keith, 1930- (Australian National University Press, 2014)
Keith Woodward has produced an inside account of the intricacies of official politics in the latter stages of the history of the Anglo-French Condominium of the New Hebrides, which will be essential reading for anyone interested in the colonial period of Vanuatu.